A Questionnaire-based Evaluation of the Awareness of Local Anaesthetics Usage and Toxicity among Surgical Specialists - Ketaki Marodkar (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Background: In 1884, when Carl Koller unveiled the role of local anaesthetic (LA) drugs, little would have anybody envisioned the vast implications these drugs would ever have in clinical practice. With the advent of daycare surgeries, the use of local anaesthetic drugs has increased manifold. However, using ultrasonography, collaborating with regional anaesthesiologists has drastically reduced the dose of LA required for loco-regional nerve blocks. Local Anaesthetic Systemic Toxicity (LAST), a serious complication of inadvertent systemic absorption of LA, encompasses a series of neurological and cardiac signs and symptoms which all surgeons should be aware of to detect it timely and also treat it using Intralipid therapy, and this knowledge is lacking. Aims and Objectives: With an aim to scrutinize this knowledge about the basic usage of LA and LAST amongst surgical consultants, this prospective, cross-sectional, questionnaire-based study was conducted. Methodology: A questionnaire containing ten questions related to the use of LA, symptomatology, and treatment of LAST was formulated, validated, and distributed amongst consultant surgeons of three teaching hospitals and among the private practicing surgeons of the city. The surgical consultants of general surgery, orthopedics, ENT, and obstetrics at the three teaching hospitals in the city who consented to participate in the study, along with consenting private practitioners of similar specializations, were included in the study. These questions tested the ability of surgeons to safely use LA and recognize and treat LAST in case they encounter it. Filled questionnaires were subjected to statistical analysis. Results: The results showed a scarcity of knowledge about safe doses of LA, the need for proper monitoring, recognizing the symptoms, and knowledge about intralipids. There was no statistically significant difference between knowledge of teaching and non-teaching surgeons or between surgeons of various specialties. Surgeons also had deficient knowledge about the use of ultrasound in regional blockades. LAST has been classically described, to begin with CNS excitation and convulsions, followed by a depressant effect on the CNS. Additionally, when knowledge about ultrasound as an aid to reduce the volume of LA was tested, the results were very unsatisfactory, with only 3-5% of surgeons having this understanding. Conclusion: The study reinforces the observations of the previous study on awareness of LAST among surgical residents. The cognition the surgeons have about safe doses of LA, perception of early symptomatology of LAST, and the awareness of Intralipid therapy for its treatment is grossly scarce. The majority of surgeons routinely use Bupivacaine, but due to inadequate knowledge about its cardiotoxic potential, the necessity to monitor the ECG of the patient is lacking. This deficiency in knowledge about LA and LAST is comparable between surgeons of teaching hospitals and those doing private practice.